Who's asking the important questions? Sexual topics discussed among young pregnant couples. - Albritton, Tashuna; Fletcher, Kyla Day; Divney, Anna; Gordon, Derrick; Magriples, Urania; Kershaw, Trace S (Journal of behavioral medicine, 2013)
The aim was to examine gender differences in sexual risk communication among young couples and factors influencing communication. Sample consisted of 296 young pregnant couples. We assessed individual, interpersonal, and community factors on sexual risk communication. The Actor-Partner Independence Model was used to assess actor and partner effects on sexual risk communication. For actor effects, being female, older, not being Hispanic, and higher condom use self-efficacy was associated with sexual risk communication. The significant partner effect was avoidant romantic attachment. Gender interactions were significant for high risk behaviors and family functioning. High risk behaviors and family functioning were associated with sexual risk communication for females but not for males. The study emphasizes the need to promote sexual risk communication among young high risk couples, particularly for males. Family support could serve as a catalyst for sexual risk communication and other sexual protective behaviors among young couples.